Przemysł metalowo-maszynowy w łódzkim okręgu przemysłowym w latach 1899-1914 - Klemantowicz, Dariusz (Acta Universitatis Lodziensis. Folia Historica, 1995)
The last twenty years of the 19th century were characterized by rapid development of industry in Łódź industrial district. Undoubtedly this development was mainly caused by the development of textile industry. However, the views of the hitherto existing literature identifying Łódź district only with textile industry seem to be wrong. Dominating textile industry stimulated the development of non-textile branches of industry including metal - machine industry which is being described. Yet, not anly textile industry decided about the development of Łódź industrial district at the end of the 19th and at the beginning of the 20th century, but other branches as well. In hitherto existing literature there have not been any works describing particular branches of industry including metal-machine industry. The aim of this article is presentation of the development of metal - machine branch in Lodz district. In 1899-1913 in Łódź industrial district an increase of contribution o f metal machine factories took place. This increase can be noticed both in the growth of production and employment and a number of factories as well. The demand for the machines for textile industry dccided about the development of metal-machine industry in the district. That is where an unusual role of the mechanic factories during the studied period and the concentration of metal-mechanic branch mainly in Łódź come from. The development of this industry in Łódź was influenced by big and great factories and to a less degree by middle-sized companies.